The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17969/agripet.v15i1.2286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Nilai Nutrisi dan Kecernaan In Vitro Pelepah Kelapa Sawit (Oil Palm Fronds) yang Difermentasi Menggunakan Aspergillus niger dengan Penambahan Sumber Karbohidrat yang Berbeda

Abstract: Oil palm frond (OPF) is one of potential sources of alternative feed, but has limited use due to high crude fiber and low crude protein contents. Fermentation is one of the methods widely applied to improve nutritive value of animal feed. The purpose of this research is to increase nutritive value of fermented oil palm fronds by adding different soluble carbohydrate source into fermentation media. The results of the experiments indicated that fermented oil palm fronds by Aspergillus niger had a significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 6 publications
0
12
0
16
Order By: Relevance
“…The highest organic matter content was application of 10% soluble carbohydrate with the average value of 98.23%. Research concocted by Wajizah et al (2015) also indicated that application of soluble carbohydrates significantly effect on organic matter due to crude protein improvement in the substrate. Luh (1991) reported that during fermentation process, yeast growth and microbial protein synthesis from metabolic process caused higher protein content in the substrate.…”
Section: Crude Fiber and Crude Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest organic matter content was application of 10% soluble carbohydrate with the average value of 98.23%. Research concocted by Wajizah et al (2015) also indicated that application of soluble carbohydrates significantly effect on organic matter due to crude protein improvement in the substrate. Luh (1991) reported that during fermentation process, yeast growth and microbial protein synthesis from metabolic process caused higher protein content in the substrate.…”
Section: Crude Fiber and Crude Proteinmentioning
confidence: 99%
“…Research conducted by Wajizah et al (2015) application of soluble carbohydrates into fermentation media improved IVDMD. It was probably due to availability of nutrients in the in vitro media and resulted in optimum growth of rumen microbial.…”
Section: Crude Fiber and Crude Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Semakin lamanya waktu inkubasi maka mikroba rumen dapat mencerna karbohidrat lebih banyak dan hasil fermentasi protein dan serat kasar pakan, sehingga konsentrasi VFA tinggi. Nilai pH rumen masih sesuai dengan pH rumen yang normal untuk berlangsungnya proses selulolisis, proteolysis, deaminasi, fermentasi pakan dan pertumbuhan mikroba rumen yaitu 6-7 (Wajizah et al, 2015;McDonald et al, 2010). Nilai pH (6,78-6,95) menunjukkan bahwa fermentasi pakan antara proporsi serat dan pati dalam rumen seimbang.…”
Section: Hasil Dan Pembahasan Nilai Ph Rumenunclassified
“…Hong et al (2015) melaporkan konsentrasi N-NH3 3 -9 mM masih bisa mendukung sintesis protein mikroba untuk pertumbuhannya. Wajizah et al (2015) melaporkan bahwa tingginya produksi VFA yang diikuti rendahnya konsentrasi amonia mencerminkan efisiensi penggunaan amonia oleh bakteri untuk sintesis protein mikroba dan pertumbuhannya. Pakan rumput gajah dan rumput laut coklat mengandung protein yang tahan degradasi sehingga menghasilkan kandungan N-NH3 yang rendah.…”
Section: Konsentrasi Amoniaunclassified